“Obtención y caracterización del almidón de la almendra del mango (mangifera indica L.) variedad criolla” - Saavedra Garcia,Jhon Kenedy (2000)
The mango <Mangifera indicia L.) Is a fruit that is? Destined for the different products elaboration. Though The flesh is the essential part of the fruit, it has Been demonstrated that the seed is used with great Profit, since of this can be extracted a starch of very Good quality for human consumption and industrial use as Was demonstrated with the analysis done to the obtained Starch. The mango, is consummated in direct form as fruit And also it is processed through the agro industrial Sectors and related industries, being rejected the seed That constitutes approximately a 17.18% of the fruit. The present investigation work, was done in order To establish the parameters adapted for the obtainment Of kernel starch of mango (Mangifera 1nd1ca L.) native Variety, by wet route, in search of giving it a value Added. This study will serve as base for subsequent Projects and will permit to recommend possible Applications in the industry. It was made the study of The raw material, of the process, and of the starch as Final product, being made physical evaluations, Chemicals, microbiology and sensitive, according to The case. The mango kernel Variety, reported in Carbohydrates (78.85%), (Hang1fera indicia L.) Native Base dries, high content in Protein (5.20%), fat (9.69%). Contain 1.87% of tannin hydrolysable, that it was Eliminated totally with solution of bisulfite of sodium To the 1% and continuous washes with water. The mango starch already purify ide contains in base Dries a 99.22% of carbohydrates, 0.13% of protein, 0.61% The most part within the limits established by ITINTEC (1974). It does not possess tannins neither toxic Preparation. The granules of kernel starch of mango <Mangifera Indicia L.) Native variety, presented increased Percentage of amylose (39.67%), the one which determined A high temperature of gelatinization (70 -86ºC) and a Curve of typical viscosity of resistant starches to the thermal treatment and of trend retrogradative, what permits to route its possible application in the nutritional gels preparation and of edible film as cover of pharmaceutical pills by its resistance to the boiling and by the gels training more f irm. The optimum processing flow was: mango seed, kernel extraction, maceration (bisulfito of sodium to the 1%), wash, pre-cuted, liquefied, sifted, sedimented, filtered, purified and dried (60ºC). It was obtained a starch respect to the mango seed. characteristic organoléptics yield of 12.32% with The very starch presented acceptable and a reduced load microbiane, demonstrating adequate hygiene Conditions employed during the processing.